2011
DOI: 10.1007/s11666-011-9639-8
|View full text |Cite
|
Sign up to set email alerts
|

Review of New Developments in Suspension and Solution Precursor Thermal Spray Processes

Abstract: Thermal spray coatings from liquid feedstock such as suspensions and solution precursors have received increasing interest due to the unique coating properties obtainable by these processes. Several research groups are working on the basis of plasma as well as on high-velocity oxy-fuel approaches to manufacture advanced nanostructured and nanophased materials. These activities are reflected in various recent publications and conference presentations about feedstock preparation, equipment and process design, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(81 citation statements)
references
References 91 publications
0
75
0
6
Order By: Relevance
“…Suspension plasma spraying has become a promising contender for the production of high performance thermal barrier coating systems, as vertically cracked [14,15], columnar [16] or highly porous coatings [17] are possible to manufacture. Suspension plasma spraying (SPS) coatings can be produced with high levels of porosity that are not normally achievable with APS or EB-PVD coatings [18].…”
Section: Introductionmentioning
confidence: 99%
“…Suspension plasma spraying has become a promising contender for the production of high performance thermal barrier coating systems, as vertically cracked [14,15], columnar [16] or highly porous coatings [17] are possible to manufacture. Suspension plasma spraying (SPS) coatings can be produced with high levels of porosity that are not normally achievable with APS or EB-PVD coatings [18].…”
Section: Introductionmentioning
confidence: 99%
“…The droplets interact first with the outer part of the plasma region, which is colder than the plasma core. This injection method is useful for large droplet sizes which may penetrate easier into the jet [17,18,33]. The study of Michaux [34] demonstrated the formation of Ni-based cermets with YSZ by SPPS using radial injection.…”
Section: Injection Of Solution Feedstockmentioning
confidence: 99%
“…Since the beginning of 21st century, there has been rapid development in nanostructured coating deposition using the SPPS process as reflected by a number of published articles [15][16][17][18][19][20][21][22]. However, most of the accounted papers focus on the deposition of ceramic materials alone and only a few have been reported on SPPS coating deposition for cermets (ceramic-metal composite) because of the oxidation potential of the metal-ions in the solution precursor [10,15].…”
mentioning
confidence: 99%
“…It has further been realized that, apart from the particles formed in-flight, any unpyrolyzed precursor impacting the preheated substrate is another crucial factor influencing the microstructure of the coating formed. The gradually improved understanding of the SPPS process in general has been well summarized in some excellent reviews that have periodically appeared in literature (Ref [49][50][51][52].…”
Section: Solution Precursor Sprayed Tbcmentioning
confidence: 99%